Vision signals and the language of vision descriptions in the prophets - Carver, Daniel E (Journal for the study of the Old Testament, 2021)
In the prophetic literature, vision descriptions (which are not to be equated with ‘vision reports’) have certain temporal and deictic orientations. Temporally, they are either past, as the vision itself is presented as past from the speech time, or present, meaning that it is described as if were occurring before the prophet’s eyes at the speech time. The spatial orientation of the text is also affected in vision descriptions as the location is in the world of the vision. Identifying a text as a vision description offers a much more coherent and meaningful interpretation of the text and fosters a deeper understanding of the text’s significance in its literary context. To that end, this study identifies two linguistic expressions that function as vision signals, that is, they indicate that the text is describing a vision. This study fills gaps in the commentary literature on the relevant texts and the literature on prophetic visions.